The diagnosis and treatment of testicular torsion in children with non-scrotal initial symptoms - Mao, Chang-Kun; Cao, Yong-Sheng; Liu, Xiang; Peng, Bo; Chu, Han; Deng, Qi-Fei; Yu, Xin; Tao, Cheng-Pin; Zhang, Tao; Yang, Chao; Peng, Shan (Frontiers in Pediatrics, 2023)
Objective To explore the clinical characteristics of testicular torsion in children with non-scrotal initial symptoms who were misdiagnosed. Methods A retrospective analysis of 73 cases children with testicular torsion and non-scrotal symptoms who were admitted to our department from October 2013 to December 2021 was performed. Patients were divided into misdiagnosis (27 cases) and clear diagnosis at first visit (46 cases) groups. Clinical data, including age at surgery, clinical presentation, physical examination, number of visits (≥2 times), affected side, time from initial symptoms to surgery, and surgical outcomes, were collected. The TWIST (Testicular Workup for Ischemia and Suspected Torsion) score was calculated and analyzed. Results Statistically significant differences between the misdiagnosis and clear diagnosis groups were seen in the time from initial symptoms to surgery, the number of visits, the degree of testicular torsion, and the rate of orchiectomy (P < 0.05). There were no statistically significant differences (P > 0.05) in age, affected side, TWIST score, guardian, direction of testicular torsion, intra-vaginal or extra-vaginal torsion, and Arda classification. Postoperative follow-up was 6–40 months. Of the 36 patients who required an orchiopexy, 1 had testicular atrophy at six months and 2 were lost to follow-up. The contralateral testis of the 37 children who underwent orchiectomies developed normally without torsion. Conclusions The clinical manifestations of testicular torsion in children are diverse and can easily lead to misdiagnosis. Guardians should be aware of this pathology and seek timely medical attention. When the initial diagnosis and treatment of testicular torsion is difficult, the TWIST score during the physical examination may be useful, especially for patients with intermediate-to-high risk scores. Color Doppler ultrasound can assist in making the diagnosis, but when testicular torsion is highly suspected, routine ultrasound is not necessary as it may lead to delayed surgical treatment.